THE PRESENCE OF PEST PARACOCCUS MARGINATUS AND NATURAL PREDATORS ON CASSAVA PLANTS IN KINTAMANI, BANGLI - I Wayan Dirgayana; Ni Nyoman Ari Putri Murtiyah (International Conference on Multidisciplinary Research Perspective, 2025)
Manihot esculenta Crantz is an important commodity in tropical regions but is vulnerable to pest attacks such as the mealybug ( Paracoccus marginatus ). This study aimed to document the occurrence of mealybugs and their natural predators in cassava agroecosystems in Kintamani, Bangli. The research was conducted from June to August 2025 in four cassava plots using a survey method. In each plot, 20 sample plants were observed, and three leaves from each plant were collected to count mealybug and predator populations. Data were analyzed to determine prevalence, density, and the relationship between predators and pests. The observations revealed that the population of P. marginatus increased over time, with the highest average density of 14.3 individuals per leaf in location 4. The overall mean population density across the four sites ranged from 7.67 to 8.71 individuals per leaf. The predator Cryptolaemus montrouzieri was found in all sites but at relatively low densities, ranging from 0.42 to 0.71 individuals per leaf. The low predator density is thought to be influenced by the presence of tending ants that protect mealybug colonies. Nevertheless, a negative correlation was observed between mealybug density and predator abundance, indicating the potential role of C. montrouzieri as a biological control agent. These findings are consistent with previous reports that predators from the Coccinellidae family play an important role in suppressing mealybug populations, although their effectiveness is strongly influenced by environmental conditions, farming practices, and interactions with other organisms. The low predator-to-pest ratio in this study area indicates that natural control capacity remains limited. Therefore, integrated biological control strategies are needed through the conservation of natural enemies, predator augmentation, and the implementation of environmentally friendly farming practices. This study highlights the importance of natural predators in supporting the sustainability of mealybug management in cassava, particularly in the highland areas of Kintamani.